(untitled) (CIPEEX, 2025)
INTRODUCTION: Syphilis is a systemic infection of compulsory notification, transmitted mainly through sexual contact with infected individuals with active lesions of the disease. The infection presents in episodes of active disease interspersed with periods of latency. Signs and symptoms vary according to each stage of the disease, which is divided into primary, secondary, latent, and tertiary. In the current scenario, there has been an increase in the number of cases. The objective of this study is to outline the clinical and epidemiological profile of syphilis in the population of the Midwest region from 2018 to 2022. METHODOLOGY: This is an observational epidemiological study of syphilis cases in the Midwest region, whose data were obtained by consulting the databases of the Notifiable Diseases Information System (SINAN). The data were collected from DATASUS regarding sociodemographic aspects (age, sex, race/color, education) and clinical data (evolution and diagnostic criteria) according to the Midwest region of Brazil. RESULTS: During the study period, 64,839 cases were reported, with 2022 having the highest number of notifications. The most affected profile was brown men, aged 20-39, with complete high school education, diagnosed by laboratory criteria and who progressed to cure. CONCLUSION: It is essential to intensify prevention campaigns, improve access to treatment, and strengthen epidemiological surveillance to reduce the burden of syphilis in the region.